Mapping provider and consumer voices using the AACTT framework: a focus group study of advance care planning - Lisa Guccione; Stephanie Best; Sonia Fullerton; Sanchia Aranda; Jill J. Francis (BMC Health Services Research)
Abstract Background The provision of healthcare is complex. When evidence-practice gaps are identified, interventions to improve practice across multi-level systems are required. These interventions often consist of multiple interacting components and behaviours. To effectively address these complexities, it is crucial to first identify the specific roles and actions required at each stage of the intervention. This approach enables a thorough examination of what is working well and what needs to be optimised. The action, actor, context, target, time (AACTT) framework provides a consistent approach to identifying key elements such as ‘who’ (actor) does ‘what’ (action), ‘where’ (context), ‘to or with whom’ (target) and ‘when’ (time). To our knowledge the AACTT has not yet been applied: 1) to specify complex interventions across patient journeys; and 2) to investigate consumer views, despite the importance of patient-centred care. Aim Using advance care planning (ACP) as an exemplar complex healthcare process, we describe a method for using the AACTT framework to 1) map a complex model of care across a patient journey 2) capture the consumer perspective; and 3) operationalise these perspectives by comparing across groups and identifying alignments or misalignments. Methods Two groups were recruited (healthcare professionals and consumers). Informed by the AACTT framework, four focus groups discussed the process of ACP across existing care pathways. Maps visually representing the perspectives and preferences of healthcare professionals and consumers were co-created iteratively. Qualitative data was deductively coded to the AACTT framework and inductively coded to identify themes within domains. Maps were circulated for critical feedback and refined. Results Healthcare professional (n-13) and consumer perspectives (n = 11) highlighted what is ‘currently occurring’ in practice, what is ‘not occurring’, and what ‘should be occurring’ to align practice with consumer preferences of care. Comparing participant perspectives identified that most misalignment occurred within the actor, context, and time domains. Misalignment was found predominantly in actions ‘occurring sometimes’, with no converging perspectives reported for the context and time domains. Conclusion This novel application of the AACTT framework systematically brings in the consumer voice in ways that may influence the delivery of care. This approach to specifying healthcare professional and consumer perspectives across a complex care pathway identifies barriers that are not found with traditional mapping methods or in current applications of the AACTT framework.